1. SUCCESSFUL HEMATOPOIETIC STEM CELL TRANSPLANTATION IN 62 CHILDREN FROM HEALTHY SIBLINGS CONCEIVED AFTER PREIMPLANTATION HLA MATCHING. (August 2019) - Umay Kara, B.; Gavaz, M.; Kumtepe Çolakoğlu, Y.; Yelke, H.; Pirkevi Çetinkaya, C.; Çetinkaya, M.; Kahraman, S.
Abstract : Introduction: The technique of PGT, coupled with HLA matching, emerged as a therapeutic tool in 2001, when it was first used for Fanconi anemia to select mutation-free and HLA identical embryos generated through IVF techniques (Verlinsky et al., 2001). In addition to allowing couples the opportunity of having an unaffected child, the technique also allows a potential donor for stem cell transplantation for the affected sibling to be selected (Grewal et al., 2004). HLA matching without mutation analysis has also been used for acquired diseases, such as acute myeloid leukemia, acute lymphoblastic leukemia, and chronic myeloid leukemia (Goussetis et al., 2011; Rechitsky et al., 2004). Material and methods: Between 2003 and 2018, 312 referred couples, with at least one child in need of HSCT, underwent PGT for HLA matching at our clinic. The referred couples applied mainly for hemoglobinopathies, hematological malignant disorders, bone marrow failure disorders, metabolic diseases and immunodeficiencies. Although the indications were diverse, the major indication for preimplantation HLA matching was beta-thalassemia. The genetic diagnosis of the disorders in children had been completed before their application to our center. A preclinical set-up study was first conducted. Before preimplantation HLA matching, HLA haplotype analysis was carried out on peripheral blood samples of the mother, father and child of each family. When available, samples from other family members were obtained, such as healthy siblings or grandparents. Results: 312 couples underwent 626 PGD for HLA matching cycles (122 HLA only and 504 single gene disorder and HLA typing cycles). Each couple has an average of 2.04 PGT cycles. A total of 114 live births were reported (128 babies born). 66 allogenic HSCT were performed, of which 62 were successful. In 57 patients, HSCT was not performed: 10 patients are awaiting HSCT, 5 children passed away while awaiting HSCT, for 15 children HSCT is not planned yet, 3 children had a HSCT from an unrelated donor, 3 children born were HLA non-identical. At the time the abstract was written detailed clinical information for 14 children were still being gathered from hematologist and 7 pregnancies were still ongoing. Conclusions: The follow up of families with affected children and siblings conceived after PGT is crucial. In the present study, full recovery was achieved after successful HSCT in 62 affected sib-lings. World-wide awareness should be increased, and the feasibility of this technique should be discussed with families as an alternative option. Preimplantation HLA matching, therefore, provides a realistic option for couples in the treatment of an affected sibling when no HLA-matched donor is available.